A Kirkpatrick-Based Evaluation Model for Islamic Values-Integrated Vocational Career Guidance - Zainul Arifin; Welly Kuswanto (Sustainable, 2026)
Vocational education is expected not only to produce technically competent graduates but also to cultivate work ethics, integrity, and moral responsibility in entering the labour market. However, career guidance evaluation in vocational schools often remains administrative and has not sufficiently assessed the internalisazion of Islamic Religious Education (IRE) values as the ethical foundation of work behaviour. This study aims to develop an evaluation model for vocational career guidance based on the integration of Islamic values through an adaptation of the Kirkpatrick framework across four levels: reaction, learning, behavior, and result. The study employed a research and development (R&D) design involving preliminary investigation, construct development, expert validation, instrument try-out, and empirical testing at SMK Nasional Malang. Data were collected through questionnaires, interviews, document analysis, and expert judgement. Quantitative analysis was conducted using PLS-SEM to examine convergent validity, discriminant validity, construct reliability, and structural relationships among the evaluation levels. The development process produced an evaluation model mapping stakeholder reactions, students' career knowledge and Islamic value learning, work-ethical behavioural change, and program impact on career readiness. PLS-SEM results indicate outer loading values of 0.721–0.904, AVE 0.641–0.774, CR 0.903–0.946, and path coefficients of beta = 0.589–0.643 (p < 0.001). The model offers an integrative evaluation framework linking career orientation, vocational competence, and Islamic work ethics as a basis for improving career guidance programs.